Sztuczna inteligencja (AI) w modyfikacjach biznesowych i niezauważone przejście od informacji do inwigilacji - Puślecki, Zdzisław W. (Humaniora. Czasopismo Internetowe, 2024)
Artificial Intelligence (AI) is becoming the foundation of IT systems and will gradually take over many decision-making processes. Passion for modern technologies is commonly combined with many years of experience gained in analyzing large data sets and creating analytical applications. Interdisciplinary teams specializing in the use of artificial intelligence and machine learning tools (Machine Learning), in particular classification and prediction models and data clustering, are formed. In the new development conditions, there were radical restrictions on social and economic activity and the emergence of new barriers, which resulted in an increase in the importance of innovative products and services based on modern technologies, aimed at overcoming the economic and social effects of the COVID-19 pandemic. Trends such as gamification, Big Data and artificial intelligence (AI) were visible. Thanks to this, the right vision was created, supported by the necessary technical knowledge to implement solutions that open the gate of undiscovered potential. Acceleration of digitization processes resulted in long-term organizational changes, including more frequent remote work of some employees. Uncertainty in the global economy caused by the pandemic has prom pated many companies reassess their development models. Instead of relying on global supply chains, more and more companies have invested in robots, resulting in a manufacturing renaissance in industrialized countries. The main aim of the study is to present artificial intelligence and the threats of its use.